Archaeology the whole story - Bahn, Paul G.; Fagan, Brian M. (Thames & Hudson, 2017)
Global in perspective and covering over four million years of history, this accessible volume provides a chronological account of both the development of the human race and the order in which modern societies have made discoveries about their ancient past. Beginning deep in prehistory, it takes in all the great archaeological sites of the world as it advances to the present day. A masterful combination of succinct analysis and driving narrative, Archaeology: The Whole Story also addresses the questions that inevitably arise as we gradually learn more about the history of our species: what are we? Where did we come from? What inspired us to start building, writing and all the other activities that we traditionally regard as exclusively human? A concluding section explains how we know what we know: for example, how seventeen prehistoric shrines were discovered around Stonehenge using magnetometers, ground-penetrating radars, and 3D laser scanners; and how DNA analysis enabled us to identify some bones discovered beneath a car park in Leicester as the remains of a fifteenth-century king of England.